Effects of fluctuating hypoxia on benthic oxygen consumption in the Black Sea (Crimean shelf). - Lichtschlag, Anna; Donis, Daphne; Janssen, Felix; Jessen, Gerdhard L; Holtappels, Moritz; Wenzhöfer, Frank; Mazulmyan, Sonia; Sergeeva, Nelly G; Waldmann, Christoph; Boetius, Antje (PANGAEA, 2015)
The outer western Crimean shelf of the Black Sea is a natural laboratory to investigate effects of stable oxic versus varying hypoxic conditions on seafloor biogeochemical processes and benthic community structure. Bottom-water oxygen concentrations ranged from normoxic (175 µmol O2/L) and hypoxic (< 63 µmol O2/L) or even anoxic/sulfidic conditions within a few kilometers' distance. Variations in oxygen concentrations between 160 and 10 µmol/L even occurred within hours close to the chemocline at 134 m water depth. Total oxygen uptake, including diffusive as well as fauna-mediated oxygen consumption, decreased from 15 mmol/m**2/d on average in the oxic zone, to 7 mmol/m**2/d on average in the hypoxic zone, correlating with changes in macrobenthos composition. Benthic diffusive oxygen uptake rates, comprising respiration of microorganisms and small meiofauna, were similar in oxic and hypoxic zones (on average 4.5 mmol/m**2/d), but declined to 1.3 mmol/m**2/d in bottom waters with oxygen concentrations below 20 µmol/L. Measurements and modeling of porewater profiles indicated that reoxidation of reduced compounds played only a minor role in diffusive oxygen uptake under the different oxygen conditions, leaving the major fraction to aerobic degradation of organic carbon. Remineralization efficiency decreased from nearly 100 % in the oxic zone, to 50 % in the oxic-hypoxic zone, to 10 % in the hypoxic-anoxic zone. Overall, the faunal remineralization rate was more important, but also more influenced by fluctuating oxygen concentrations, than microbial and geochemical oxidation processes.
High-resolution in situ oxygen microprofiles, porewater and solid phase geochemistry from the Crimean shelf (Black Sea) from Maria S. Merian cruise MSM15/1
Keywords: HYPOX; In situ monitoring of oxygen depletion in hypoxic ecosystems of coastal and open seas and land-locked water bodies